Preliminary Evidence of a Dose-Response for Continuing to Play on Recovery Time After Concussion. Issue 2 (March 2020) - Charek, Daniel B.; Elbin, R. J.; Sufrinko, Alicia; Schatz, Philip; D'Amico, Nathan R.; Collins, Michael W.; Kontos, Anthony P.
Abstract : Objective: To investigate a dose-response relationship between continuing to play following concussion and outcomes. Participants: A total of 130 athletes (age 11-19 years). Design: Repeated-measures design comparing symptoms, neurocognitive performance, and recovery time between 52 athletes immediately removed from play (Removed), 24 who continued to play for 15 minutes or less (Short-Play), and 32 who continued to play for more than 15 minutes (Long-Play). Main Measures: Recovery was the number of days from injury to clearance. Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) measured neurocognitive outcomes and the Post-Concussion Symptom Scale (PCSS) measured symptom severity. Results: Long-Play (44.09 ± 27.01 days) took longer to recover than Short-Play (28.42±12.74 days) and Removed (18.98 ± 13.76 days). Short-Play was 5.43 times more likely, and Long-Play 11.76 times more likely, to experience protracted recovery relative to Removed. Both Play groups had worse neurocognitive performance and higher symptom scores than Removed at days 1 to 7, with Long-Play demonstrating worse reaction time than Short-Play. At days 8 to 30, both Play groups performed worse than Removed on visual memory and visual motor speed, while only Long-Play performed worse on verbal memory and reaction time. Conclusions: Results provide initial evidence of a dose-response effect for continuing to play on recovery from concussion, highlighting the importance of removal from play.